Colorectal Cancer Diagnosis Improvement Project Evaluation Demonstrates the Importance of Using Multiple Measures to Track Progress Toward Timeliness Goals. Issue 3 (22nd December 2011) - Partin, Melissa R.; Powell, Adam A.; Nugent, Sean; Ordin, Diana L.
Abstract Using data from an improvement collaborative, we examined whether facility‐specific conclusions regarding the success of efforts to improve timely access could vary depending on the type of measure used. The sample was drawn from 21 Veterans Health Administration (VHA) medical facilities participating in a collaborative on timely diagnostic evaluation following positive fecal occult blood tests (FOBT+). We identified FOBT+ cases from participating facilities between September 2004 and August 2005 (precollaborative), and September 2006–August 2007 (postcollaborative). Dates of FOBT+ results, colonoscopy, and death were extracted from VHA medical records. We estimated the cumulative proportion receiving colonoscopy within 2 months of the FOBT+ (target measure established by collaborative), and compared facility‐specific results regarding improvement on this measure to results from measures of the cumulative proportion receiving colonoscopy within 12 months, and average time‐to‐colonoscopy. In 12 facilities (57%), all measures suggested consistent results regarding pre–post collaborative changes in colonoscopy rates. In four facilities (19%), the target measure suggested less favorable change, and in five (24%), more favorable change than one or both other measures. Because conclusions drawn about the success of QI efforts can vary by the measure used, multiple measures should be employed to track progress toward timeliness goals.